2008
DOI: 10.1016/j.oceaneng.2008.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Historical tsunami in the Makran Subduction Zone off the southern coasts of Iran and Pakistan and results of numerical modeling

Abstract: Tsunami hazard in the Makran Subduction Zone (MSZ), off the southern coasts of Iran and Pakistan, was studied by numerical modeling of historical tsunami in this region. Although the MSZ triggered the second deadliest tsunami in the Indian Ocean, among those known, the tsunami hazard in this region has yet to be analyzed in detail. This paper reports the results of a risk analysis using five scenario events based on the historic records, and identifies a seismic gap area in western Makran off the southern coas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(107 citation statements)
references
References 42 publications
1
100
0
Order By: Relevance
“…This tsunami event was recorded on instrument for the first time in this region. This was the only event in MSZ for which the data of the magnitude of earthquake and run-up heights in different coasts is recorded [9][10][11][12][13][14][15]. The tsunami hazard parameters of 1945 earthquake are as follows:…”
Section: Commit Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This tsunami event was recorded on instrument for the first time in this region. This was the only event in MSZ for which the data of the magnitude of earthquake and run-up heights in different coasts is recorded [9][10][11][12][13][14][15]. The tsunami hazard parameters of 1945 earthquake are as follows:…”
Section: Commit Resultsmentioning
confidence: 99%
“…The tsunami was also recorded at Muscat and Gawader. This is the only event in Makran subduction zone for which the instrumental data is available such as data about the magnitude of earthquake and run-up values at different coasts [9]. …”
Section: Historic Tsunamimentioning
confidence: 99%
“…Arabian Sea coasts have been affected by numerous and disastrous tsunamis in the past (Jourdan, 2008;Heidarzadeh et al, 2008;Donato et al, 2008Donato et al, , 2009Jaiswal et al, 2009;Pilarczyk et al, 2011;Pilarczyk and Reinhardt, 2012) and storm waves from cyclones (Fritz et al, 2010). The main tsunami source in the Arabian Sea is the seismic activity of the Makran subduction zone, which caused the 1945 event (M w = 8.1) and the subsequent 4000 human fatalities.…”
Section: Introductionmentioning
confidence: 99%
“…This zone extends east from the Strait of Hormoz in Iran to near Karachi in Pakistan with a length of about 900 km. The reasons that we have chosen the MSZ for our case study are twofold: firstly, Heidarzadeh et al (2008) presented evidence that a splay fault may have been responsible for the huge runup heights observed in the near field during the Makran earthquake and tsunami of November 27, 1945, and secondly, Mokhtari et al (2008) showed that many splay faults are present in the MSZ using 2D seismic reflection profiles. Figure 7 is an example of the 2D seismic reflection profiles presented by Mokhtari et al (2008).…”
Section: Modelling the Effect Of Splay Fault Branching On Tsunami Wavesmentioning
confidence: 99%